Ratification of ICRMW toward the ILO Conventions amid COVID-19 in Thailand - Siwarut Laikram; Shubham Pathak (Emerging Science Journal, 2022)
Globalization has opened the avenues for the world to come together and attain sustainable growth. Migrant workers are a lifeline for several countries' labour forces and productivity. However, in Thailand, the rights of these migrants are restricted due to the non-ratification of the International Convention on the Protection of the Rights of Migrant Workers and Family Members (ICRMW). This research explores and analyzes various factors essentially responsible for the ratification of ICRMW in Thailand. The methodology adopted is the mixed method. The collected data were analyzed based on a socio-legal approach, with qualitative and quantitative tools and techniques combined: the strength, weakness, opportunity, and threats (SWOT) technique was integrated into the analytic hierarchy process (AHP) (SWOT-AHP). The findings suggest that Thailand has not yet ratified the ICRMW conventions, including ILO C-87 and ILO C-98, thus depriving migrant workers of protection. They are not protected by national law and are not entitled to equal protection as nationals: for instance, foreign workers are forbidden from migrating to the established labour unions and enjoying medical benefits and salaries. All these must be consistent with the conventions, particularly the Labor Protection Act, B.E. 2541 (1998) and the Labor Relations Act B.E. 2518 (1998). The novelty of this research is the analysis of the domestic and international laws in the Thai context, which depicts the need for ratification of ICRMW to protect migrant workers and their families. The findings can pave the way for similar future research in other ASEAN member countries. Doi: 10.28991/esj-2022-SPER-014 Full Text: PDF